Spiritualitas Kepemimpinan dalam Pengelolaan Pendidikan dan Pembelajaran - Arfandi Arfandi (Program Pascasarjana Universitas Ibrahimy, 2019)
Spirituality in leadership is a leadership that leads the worldly dimension to the spiritual dimension. God is a true leader who inspires all deeds, influences and moves the conscience of His servants. Spirituality in leadership is leadership that forms values, attitude, behavior needed for intrinsic motivation to achieve a sense of spiritual survival. Spirituality-based leadership is not only about intelligence and skills in leadership, but also about the values of truth, honesty, integrity, creativity, wisdom, compassion. Spirituality in leadership is the way of a leader to pays attention to how other people can grow, develop and achieve the vision. There are three dimensions of spirituality in leadership they are first, the activities carried out by a manager (leader, head, chairman and others) with other people or groups. Second, the activities have purposes and third, management is carried out in the organization, so that so that becomes organization oriented. Therefore, the spirituality in leadership in the management of learning and education has significant impact on teachers, students, stakeholders, etc.